KOREOGRAFI KELOMPOK: MEDIA PEMBENTUKAN NILAI KARAKTER - Bulan, Indra (Studi Budaya Nusantara, 2020)
This study highlights group choreography material in learning, whether at the elementary, junior high, or high school level. Character values are one of the main objectives of the learning process. One way to achieve this is by providing dance lessons in the form of group choreography. Group choreography is a dance performed by a group of dancers consisting of at least two people. Values such as discipline, cooperation, responsibility, etc. can be realised by learning group choreography.